Ethno-Nationalism In Post-Suharto Indonesia: The Chinese Question - Ricardo, Ricky (2012)
The purpose of this study is to identify the development of ethno-nationalists’ sentiments, organizations and movements performed by the Chinese elites in Indonesia during post-Suharto era and their influence on Indonesian politics. If compared to most ethno-nationalist groups in Indonesia, Chinese nationalists are considered unique due to their origin as immigrants; Chinese community do not have strong ancestry attachment to Indonesia as their homeland. Therefore, the author wants to find out what motivates the Chinese elites to express their ethnic sentiment especially when such sentiments were not present during the Suharto regime.